Effects of different doses of dexamethasone as local anesthetic adjuvant on brachial plexus block: A protocol for systematic review and meta analysis. Issue 17 (30th April 2021) - Zhang, Shuai; Song, Meiyan; An, Wei; Wang, Zhongyi
Abstract: Background: Dexamethasone has been widely used in brachial plexus block to enhance the effects of brachial plexus block. However, the clinical findings are not consistent with the dosage of dexamethasone prolonging local anesthetic nerve block. Therefore, the purpose of this study was to explore the effects of different doses of dexamethasone as local anesthetic adjuvant on brachial plexus block through network meta-analysis. Methods: We searched PubMed, Web of Science, Cochrane Library, and Embase databases to collect all randomized controlled trials (RCTs) of different doses of dexamethasone as local anesthetic adjuvant on brachial plexus block until March 2021. Two researchers then independently screened articles, extracted data, and evaluated the quality of selected literatures. All data was processed by Stata 14.0 and WinBUGS 1.4.3.software. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: Our study is expected to provide high-quality evidence-based medicine advice for the effects of different doses of dexamethasone as local anesthetic adjuvant on brachial plexus block. Ethics and dissemination: Ethical approval was not required for this study. The systematic review will be published in a peer-reviewed journal, presented at conferences, and shared on social media platforms. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/PZ5WR.